UX for AI : a framework for designing AI-driven products - Nudelman, Greg (John Wiley & Sons, Inc., 2025)
Learn to research, plan, design, and test the UX of AI-powered products Unlock the future of design with UX for AI--your indispensable guide to not only surviving but thriving in a world powered by artificial intelligence. Whether you're a seasoned UX designer or a budding design student, this book offers a lifeline for navigating the new normal, ensuring you stay relevant, valuable, and indispensable to your organization. In UX for AI: A Framework for Designing AI-Driven Products, Greg Nudelman--a seasoned UX designer and AI strategist--delivers a battle-tested framework that helps you keep your edge, thrive in your design job, and seize the opportunities AI brings to the table. Drawing on insights from 35 real-world AI projects and acknowledging the hard truth that 85% of AI initiatives fail, this book equips you with the practical skills you need to reverse those odds. You'll gain powerful tools to research, plan, design, and test user experiences that seamlessly integrate human-AI interactions. From practical design techniques to proven user research methods, this is the essential guide for anyone determined to create AI products that not only succeed but set new standards of value and impact. Inside the book: Hands-on exercises: Build your confidence and skills with practice UX design tasks like Digital Twin and Value Matrix, which you can immediately apply to your own AI projects. Common AI patterns and best practices: Explore design strategies for LLMs (Large Language Models), search engines, copilots, and more. Proven user research strategies: Learn how to uncover user needs and behaviors in this brave new world of AI-powered design. Real-world case studies: See how simple, practical UX approaches have prevented multimillion-dollar failures and unlocked unprecedented value. Perfect for any UX designer working with AI-enabled and AI-driven products, UX for AI is also a must-read resource for designers-in-training and design students with an interest in artificial intelligence and contemporary design.
Keywords: User-centered system design.; Artificial intelligence.; elektronické knihy; electronic books